2021
DOI: 10.1088/1572-9494/ac01db
|View full text |Cite
|
Sign up to set email alerts
|

A design of novel photonic crystal fiber with low and flattened dispersion for supporting 84 orbital angular momentum modes

Abstract: A dual-guided photonic crystal fiber (PCF) with low and flattened dispersion is designed, which can support a large number of orbital angular momentum (OAM) modes. The properties of the proposed PCF are systematically analyzed through the finite element method. The results show that the proposed PCF can support up to 84 OAM modes with 600 nm bandwidth ranging from 1000 to 1600 nm. All values of mode purity are above 91.7%, the isolation parameters are larger than 67 dB and the maximum value up to 145 dB, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These perform excellently and are easy to manufacture. Some PCF designs with air holes are as follows: A total of 84 OAM modes [154], 110 OAM modes [155], and 166 OAM modes [156].…”
Section: Photonic Crystal Fibers (Pcf)mentioning
confidence: 99%
“…These perform excellently and are easy to manufacture. Some PCF designs with air holes are as follows: A total of 84 OAM modes [154], 110 OAM modes [155], and 166 OAM modes [156].…”
Section: Photonic Crystal Fibers (Pcf)mentioning
confidence: 99%
“…-Ring (or annular)-core optical fibers (pure silica core and cladding with the inclusion of a high refractive index material layer on the core/cladding boundary) [1][2][3][7][8][9][10][11][12][13]; -Ring-core MOFs and PCFs (silica center, bounded by a ring from material/glass (doped silica) with a higher refractive index, and air holes in the periphery) [14,15]; -Hollow-core MOFs and PCFs, also known as hollow-core photonic bandgap fibers (pure silica circular fiber with large air central hole (e.g., "core") and small air holes in the periphery part, placed according to desired designed geometry) [1,2,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]; -Anti-resonant hollow-core fiber (AR-HCF) with complicated geometry: so-called "revolver" fibers-single/double/triple-ring AR-HCF and single/double noodles nested AR-HCF [3,29,[32][33][34] and nodeless nested AR-HCF [3,29,32,33,35,36], "grapefruit" [37,38], "ice-cream"…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Allen et al [1] indicated that an electromagnetic wave may carry orbital angular momentum (OAM), and when propagating in a vacuum, it can transfer its OAM to particles if the wave is absorbed. Subsequently, growing interest has been given to the study of photon OAM states, which are generated in light waves [2][3][4][5]. It is widely known that the angular momentum of electromagnetic radiation has two distinct components.…”
mentioning
confidence: 99%